2017
DOI: 10.1515/ntrev-2016-0101
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic targeting with superparamagnetic iron oxide nanoparticles for in vivo glioma

Abstract: The purpose of this study was to review the use of the magnetic targeting technique, characterized by magnetic driving compounds based on superparamagnetic iron oxide nanoparticles (SPIONs), as drug delivery for a specific brain locus in gliomas. We reviewed a process mediated by the application of an external static magnetic field for targeting SPIONs in gliomas. A search of PubMed, Cochrane Library, Scopus, and Web of Science databases identified 228 studies, 23 of which were selected based on inclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…In recent years, nanomedicine has attracted increasing attention in cancer treatment research, due to its potential for significant cost savings and pain reduction compared to traditional therapies . Magnetic nanoparticles (NPs) are important nanomaterials, and due to their magnetic properties and biocompatibility, they have been widely used for cell separation, cell guidance, drug delivery, , and hyperthermia; , in biosensors; and as contrast agents in magnetic resonance imaging (MRI). , Iron-based materials are preferred due to their ease of fabrication and coating, magnetic properties, and ability to absorb an 808 nm laser and convert it into heat . In addition, it is an approved material for clinical use by the Food and Drug Administration (FDA), making it attractive for biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nanomedicine has attracted increasing attention in cancer treatment research, due to its potential for significant cost savings and pain reduction compared to traditional therapies . Magnetic nanoparticles (NPs) are important nanomaterials, and due to their magnetic properties and biocompatibility, they have been widely used for cell separation, cell guidance, drug delivery, , and hyperthermia; , in biosensors; and as contrast agents in magnetic resonance imaging (MRI). , Iron-based materials are preferred due to their ease of fabrication and coating, magnetic properties, and ability to absorb an 808 nm laser and convert it into heat . In addition, it is an approved material for clinical use by the Food and Drug Administration (FDA), making it attractive for biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of this active targeting is the reduction of side effects in healthy cells and tissues [ 19 ]. Most in vivo studies have demonstrated successful targeting of MNPs towards the tumor by the application of an SMF of a strength between 0.2 and 0.6 T, with different times of application ranging from 30 min [ 65 ] to 48 h [ 66 ]. In this work, we studied the effect of the presence of an SMF generated by a magnet of 0.3 T during the incubation of vGPCR cells with two concentrations of MAG.PEG for 48 h. Our results revealed that the pattern of distribution of the MNPs in the cell cultures exposed to the SMF is different from that observed in the absence of the magnet.…”
Section: Discussionmentioning
confidence: 99%
“…Both nanoparticles have the benefits of easy synthesis and surface functionalization, [ 53 ] and serve as contrast agents to enhance imaging and achieve image-guided therapy [ 55 , 56 , 57 ]. Additionally, SPIONs exhibit the advantageous property of magnetic targeting via an external magnetic field for spatial targeting [ 58 ]. Venditti et al reported that GNPs are used to improve the bioavailability of drugs [ 59 ].…”
Section: Smart Drug Delivery Nanocarriersmentioning
confidence: 99%